FEATURES OF THE APPLICATION OF STEM APPROACH IN THE EDUCATIONAL PROCESS OF PRIMARY SCHOOL - Zhigailo, Oksana (Physical and Mathematical Education, 2021)
Formulation of the problem. The rapid development of all spheres of human life, the intensive use of computer technologies and robot engineering in the modern world make the necessary specifics of the educational process at all levels of the national institutions of secondary education. The introduction of STEM approach into the educational process of primary school to develop intellectual abilities and cognitive and research activities of schoolchildren is one of the promising directions of the modernization of educational system. This problem is insufficiently developed, For its detailed solution it needs the acquirement of knowledge in various fields of science, programme technologies, as well as the directions of STEM education.Materials and methods. The following research methods were used during the preparation of the article: comparative analysis of theoretical statements revealed in the studied scientific and educational literature; observation of the educational process of national primary school.Results. To achieve the goal it is proposed to use the STEM approach in the educational process of primary school, to introduce training modules using elements of the analyzed approach for the complex solution of such specific tasks as the development of intellectual abilities of schoolchildren during their cognitive and research activities and also their participation in scientific and technical creativity.Conclusions. Introduction the main components of STEM education into the curricula of modern national institutions of secondary education enables to create the best environment for the discovering and development of schoolchildren’s creative potential. The use of STEM technologies at primary school is the most expedient at the elementary, propedeutical level. The STEM approach has great advantages, namely, a) it intensifies the interest in mathematics and natural science; b) it motivates to gain knowledge in the field of technics, robot engineering, design; c) it promotes the development of primary schoolchildren’s creative abilities and communication skills, and it furthers early identification of their personal potential and future orientation.
Keywords: STEM education; primary school; Mathematics lesson; STEM – STEAM – STREAM approaches